Violência doméstica: os abusos invisíveis e feminicídio - Remuzzi, Maísa Ferro (2024)
This article aims to analyze an overview of domestic violence against women, some data regarding the number of victims, and their species. It seeks to differentiate the 5 (five) existing types of domestic violence, in order to identify how they usually occur in everyday life. Furthermore, we intend to discuss invisible abuse as a manifestation of violence against women, as sometimes this does not only occur physically. Likewise, we seek to analyze how the invisibility of cases occurs, a fact that makes it difficult to protect the victim. Furthermore, it aims to discuss the most serious manifestation of domestic violence, which is feminicide, its legal classification, and the impact it has on the lives of descendants who witness such cruelty.